Penyuluhan dan pelatihan kewirausahaan sebagai upaya peningkatan intensi berwirausaha pada UKM ”Bangkit” - Surahma Asti Mulasari; Fatwa Tentama; Sulistyawati; Tri Wahyuni Sukesi; Herman Yuliansyah; Lu'lu' Nafiati (Universitas Lancang Kuning, 2021)
Covid-19 has had a major impact on all aspects of life and in all fields. Since Covid-19 was declared a pandemic, there have been many impacts of Covid-19 and the most pronounced impact has been on the Small and Medium Enterprises (SME) sector. The aim of this program is to provide counseling and training to increase entrepreneurial intentions in “Rise” SMEs in the midst of the Covid-19 pandemic. The target of this program is the people of Ngoro-Oro village who are members of UKM